Patient‐reported experience measures are essential to improving quality of care for chronic wounds: An international qualitative study. Issue 4 (21st April 2020) - Squitieri, Lee; Tsangaris, Elena; Klassen, Anne F.; van Haren, Emiel L. W. G.; Poulsen, Lotte; Longmire, Natasha M.; van Alphen, Tert C.; Hoogbergen, Maarten M.; Sorensen, Jens Ahm; Cross, Karen; Pusic, Andrea L.
Abstract: Traditional quality measures for chronic wounds have focused on objective outcomes that are challenging to risk adjust, lack patient input, and have limited ability to inform quality improvement interventions. Patient‐reported experience measures (PREMs) provide information from the patient perspective regarding health care quality and have potential to improve patient‐centredness, increase care efficiency, and generate actionable data for quality improvement. The purpose of this study was to understand patient experiences and health care processes that impact quality of care among patients with chronic wounds. Sixty patients at least 18 years of age with various wound aetiologies were recruited from Canada, Denmark, The Netherlands, and the United States as part of a larger phase 1 qualitative study to develop a patient‐reported outcome measure for chronic wounds (WOUND‐Q). All patients had a chronic wound for at least 3 months, were fluent in their native speaking language, and able to participate in a one‐on‐one semi‐structured interview. Interviews were digitally recorded and transcribed verbatim. Interpretive description was used to identify recurrent themes relating to patient experience and quality of care. We identified five domains (care coordination, establishing/obtaining care, information delivery, patient‐provider interaction, and treatment delivery) and 21 sub‐domains (access to patient information, interdisciplinary communication, encounter efficiency, provider availability, specialist referral, staff professionalism, travel/convenience, modality, reciprocity, understandability/consistency, accountability, continuity, credentials, rapport, appropriateness, complication management, continuity, environment/setting, equipment and supply needs, expectation, and patient‐centred) as potential opportunities to measure and improve quality of care in the chronic wound population. PREMs for chronic wounds represent an important opportunity to engage patients and longitudinally assess quality across clinical settings and providers. Future research should focus on developing PREMs to complement traditional objective and patient‐reported outcome measures for chronic wounds.